The Oxford handbook of political leadership - Rhodes, R. A. W.; Hart, Paul 't (Oxford Oxford University Press, 2014)
Political leadership has returned to the forefront of research in political science in recent years, after several years of neglect. This handbook provides a broad-ranging and cohesive examination of the study of political leadership.
Puzzles of political leadership / R.A.W. Rhodes and Paul 't Hart -- Western political thought / Nannerl O. Keohane -- Theory of democratic leadership / Frank Hendriks and Niels Karsten -- Confucianism / Joseph Chan and Elton Chan -- Feminism / Laura Sjobert -- Political science / David S. Bell -- Public administration / R.A.W. Rhodes -- Political psychology / Margaret G. Hermann -- Psychoanalytic theories / Stanley A. Renshon -- Social psychology / Stephen D. Reicher, S. Alexander Haslam, and Michael J. Platow -- Rational choice approaches to leadership / Geoffrey Brennan and Michael Brooks -- Anthropology / Cris Shore -- Institutional analysis / Ludger Helms -- Contextual analysis / Paul 't Hart -- Decision analysis / David Brulé, Alex Mintz, and karl DeRouen Jr. -- Social-constructionist analysis / Keith Grint -- Rhetorical and performative analysis / John Uhr -- Experimental analysis / Rose McDermott -- Observational analysis / Francesca Gains -- At-a-distance analysis / Mark Schafer -- Biographical analysis / James Walter -- Personality profiling analysis / Jerrold M. Post -- Civil leadership / Richard A. Couto -- Party and electoral leadership / Marina Costa Lobo -- Populism and political leadership / Cas Mudde and Cristóbal Rovira Kaltwasser -- Performative political leadership / John Gaffney -- Political leadership in networks / Eric-Hans Jlijn -- Political leadership in times of crisis / Chris Ansell, Arjen Boin, and Paul 't Hart -- Leadership and the American presidency / David McKay -- Presidential communication from hustings to Twitter / Jeffrey E. Cohen -- Executive leadership in semi-presidential systems / Robert Elgie -- The variability of prime ministers / Patrick Weller -- The contingencies of prime-ministerial power in the UK / Andrew Blick and George Jones -- Prime ministers and their advisers in parliamentary democracies / Chris Eichbaum and Richard Shaw -- Cabinet ministers : leaders, team players, followers? / Rudy B. Andeweg --Local political leaders / Colin Copus and Steve Leach -- Local political leadership / John Wanna -- Leadership and international cooperation / Charles F. Parker and Christer Karlsson -- Leadership of international organizations / Bob Reinalda and Bertjan Verbeek -- Political leadership in China / Bo Zhiyue -- Latin American leadership / Harvey F. Kline -- Post-communist leadership / Leslie Holmes -- African political leadership / Gerrie Swart, Jo-Ansie van Wyk, and Maryke Botha -- Can political leadership be taught? / Jean Hartley -- Does gender matter? / Patricia Lee Sykes -- What have we learned? / Jean Blondel.
Includes bibliographical references and indexes.
Keywords: Political leadership; Politics and Government